Cognitive reserve and regional brain volume in amyotrophic lateral sclerosis. (June 2021) - Temp, Anna G.M.; Prudlo, Johannes; Vielhaber, Stefan; Machts, Judith; Hermann, Andreas; Teipel, Stefan J.; Kasper, Elisabeth
Abstract: Objective: We investigated whether cognitive reserve measured by education and premorbid IQ allows amyotrophic lateral sclerosis patients to compensate for regional brain volume loss. Methods: This was a cross-sectional study. We recruited sixty patients with amyotrophic lateral sclerosis from two specialist out-patient clinics. All participants underwent neuropsychological assessment; the outcomes were standardized z-scores reflecting verbal fluency, executive functions (shifting, planning, working memory), verbal memory and visuo-constructive ability. The predictor was regional brain volume. The moderating proxies of cognitive reserve were premorbid IQ (estimated by vocabulary) and educational years. We hypothesized that higher cognitive reserve would correlate with better performance on a cognitive test battery, and tested this hypothesis with Bayesian analysis of covariance. Results: The analyses provided moderate to very strong evidence in favor of our hypothesis with regard to verbal fluency functions, working memory, verbal learning and recognition, and visuo-constructive ability (all BF01 > 3): higher cognitive reserve was associated with a mild increase in performance. For shifting and planning ability, the evidence was anecdotal. Conclusions: These results indicate that cognitive reserve moderates the effect of brain morphology on cognition in ALS. Patients draw small but meaningful benefits from higher reserve, preserving fluency, memory and visuo-constructive functions. Executive functions presented a dissociation: verbally assessed functions benefitted from cognitive reserve, non-verbally assessed functions did not. This motivates future research into cognitive reserve in ALS and practical implications, such as strengthening reserve to delay decline.